POLA KOMUNIKASI VIRTUAL DALAM PENGGUNAAN E-SPORT GAMES (STUDI KASUS : MOBILE LEGENDS DI KALANGAN MAHASISWA ILMU KOMUNIKASI UIN SUMATERA UTARA) - Muhammad Al Fayyad; Solihah Titin Sumanti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This research purpose to know the Virtual Communication Patterns of the game Mobile Legends in the University of Communication Studies of UINSU. The research uses descriptive qualitative research methods with a virtual ethnographic approach. Data collection using interviews to 5 sources and library studies. The results of the research showed that the virtual communication pattern of the Mobile Legends game uses Whatssapp media and game conversation media to invite UINSU Communication Sciences students to play, discuss, and give commands and instructions while the game is taking place using Mobile Legend conversation media using everyday, gaul and informal language as well as using stickers or emoticons available on both media. But few use direct or face-to-face communication. Reactions or feedback obtained such as expressing anger when losing in a game and using words unpolite, happy or happy at the time of winning the game, each player can give instructions and orders at the moment of the game subsug so that they follow the instructions in order to win the game. The communication pattern they use is a network of all channels, because anyone can communicate with others in the game.